INVESTIGATING THE IMPACT OF MULTIMODAL TEXT ON STUDENTS’ READING COMPREHENSION IN ENGLISH LEARNING - Andita Apriliasari; Pipit Novita (LPPM Universitas PGRI Jombang, 2024)
The purpose of this research is to investigate the impact of multimodal text on students' reading comprehension in learning English at SMP Islam As Sakinah. Therefore, the research methodology used in this research is quantitative with a pre-experimental design. The sample was selected through cluster random sampling by only taking one class consisting of 30 students from a class 7 population of 92 students. Data was collected using pre-test and post-test with 10 questions. The results of this research analysis showed that sig. value is known. (2-tailed) of 0.000. the sig. (2-tailed) < 0.05 or 0.000 < 0.05 the hypothesis H0 is rejected and Ha is accepted because there is a significant difference between the pre-test and post-test learning outcomes. So from these results it can be concluded that the pre test and post test data are normally distributed and there is an influence of the use of multimodal texts in developing students' reading comprehension in English learning.